Determinants and Pathways of Nitrous Oxide Emissions from Soil Irrigated with Reclaimed Water - Yanbing Chi; Chenchen Wei; Peiling Yang; Ning Ma (Agronomy)
Reclaimed water (RW), as a reliable and renewable secondary water source, has become a crucial strategy for many countries to supplement agricultural water usage and alleviate water scarcity. However, despite the increasing use of RW, there has been limited research on the factors affecting soil nitrous oxide (<semantics>N2O</semantics>) emissions under RW irrigation. Understanding these factors is essential for guiding RW irrigation practices and controlling greenhouse gas emissions. This research, conducted from 2014 to 2015, includes field experiments designed to systematically assess the effects of soil chemistry properties and temperature on soil <semantics>N2O</semantics> emissions under RW irrigation. Subsequent to these field studies, soil samples were collected for 15N isotope trials to examine the impact of RW on the soil <semantics>N2O</semantics> production process, including autotrophic nitrification, heterotrophic nitrification, and denitrification. The results showed that RW irrigation influenced soil <semantics>N2O</semantics> emissions by affecting soil pH, but not through changes in soil total nitrogen (TN) or soil organic carbon (SOC) content. Moreover, compared to groundwater (UW) irrigation, RW irrigation significantly reduced the temperature sensitivity of soil <semantics>N2O</semantics> emissions. The 15N isotope labeling trial indicated that autotrophic nitrification was the primary pathway for soil <semantics>N2O</semantics> production under RW irrigation, contributing 60.46%—significantly higher than that observed with UW irrigation. Primary treated sewage (PW) significantly increased soil <semantics>N2O</semantics> emissions through the heterotrophic nitrification process compared to RW, with contributions rising from 11.31% to 13.23%. Additionally, RW, compared to UW, significantly increased the copy numbers of soil nitrification genes (ammonia-oxidizing archaea [AOA-amoA]) and denitrification genes (nitrite reductase [nirK and nirS]). Therefore, it is important to appropriately control the nitrification process and balance soil pH to manage soil <semantics>N2O</semantics> emissions under RW irrigation.